The Exit-Voice Tradeoff in the Labor Market: Unionism, Job Tenure, Quits, and Separations - Freeman, Richard B. (Quarterly Journal of Economics, 1980)
This paper examines the effect of trade unionism on the exit behavior of workers in the context of Hirschman's exit-voice dichotomy. Unionism is expected to reduce quits and permanent separations and raise job tenure by providing a "voice " alternative to exit when workers are dissatisfied with conditions. Empirical evidence supports this contention, showing significantly lower exit for unionists in several large data tapes. It is argued that the grievance system plays a major role in the reduction in exit and that the reduction lowers cost and raises productivity. In the exit-voice model of the social system [Hirschman, 1970, 1976] individuals react to discrepancies between desired and actual social phenomena in one of two ways: by the traditional free market mechanism of "exiting " from undesirable situations; or by directly expressing their discomfort to decision-makers through "voice. " While little attention is paid to the labor market in Hirschman's book [1970], the exit-voice dichotomy provides a potentially fruitful framework for analyzing the major employee institution of capitalist economies—the trade union. From the perspective of the dichotomy, voice is embodied in unionism and the collective bargaining system by which workers elect union leaders to represent them in negotiations with management, while exit consists primarily of quits. A major feature of the model is a predicted tradeoff between the two adjustment mechanisms: when workers have a voice institution for expressing discontent, they should use the exit option less frequently and thus exhibit lower quit rates and longer spells of job tenure with firms. Is unionism associated with lower quit rates and higher job tenure of workers, as predicted by the model? Po what extent can any reduction in quits due to unionism he attributed to union "voice " as opposed to other routes of union effects, notably wage gains? Despite a sizeable literature on labor turnover and on the economic effects of unions, extant empirical evidence provides no clear answer to these questions. The turnover literature has focused on quit rates for aggregated manufacturing industries, which provides only